PENGEMBANGAN PRODUK KENCUR SEBAGAI SUMBER ANTIOKSIDAN DALAM PRODUK MAKANAN RINGAN: STIK KENCUR PADA PROGRAM WMK UNTAG SURABAYA - Retha Putri Wilujeng; Diana Juni Mulyati (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
In the modern era, there is a growing trend toward innovative snack products made from natural ingredients, driven by increasing consumer health consciousness. This research focuses on developing kencur (Stik Kencur) as a healthy snack rich in antioxidants, particularly flavonoids. As part of the Program Wirausaha Merdeka (WMK) at the 17 August 1945 University of Surabaya, the study aims to explore the potential of kencur-based snacks through a qualitative approach combined with SWOT analysis. The research investigates market trends, consumer perceptions, and the challenges in product development to assess the viability and prospects of Stik Kencur as a competitive healthy snack option.